Membangun Karakter Bangsa Dari pesantren: Studi Pemikiran Hasyim Asy’ari tentang Pendidikan Karakter - Sholihuddin, Ahmad (Al-Riwayah : Jurnal Kependidikan, 2015)
The purpose of this study is to describe a competence-based education in pesantren in general. As part of the community, pesantren with typical main elements such as kiai, santri, mosque, cottage and classical instruction books (kitabkuning), has become its own subculture. Therefore, despite modernization and globalization invaded, pesantren can still maintain its existence. Furthermore, many stakeholders indicated that the pesantren is educational institutions that can serve as a model of character education in Indonesia. How are the strategies and patterns of character education by pesantren so as to create culture? What are these cultures? Commanlly, Hasyim Asyary is leader of perantrean. This article explores Hasim Asyari’ thought on his contribution in character building of nation